Effectiveness of the 2P3F Health Literacy Program for overweight management among late adolescents in Thailand: A quasi-experimental study - Piyanan Narmkul; Thamarak La-ongnual; Somkiattiyos Woradet; Nopparat Songserm (International Journal of Public Health Asia Pacific, 2026)
Background: Overweight and obesity in late adolescence are growing public health concerns in Thailand, increasing the risk of chronic diseases. Health literacy has been recognized as a critical factor influencing health behaviours, yet limited interventions have focused on enhancing health literacy among Thai adolescents. Objectives: This study aimed to evaluate the effectiveness of the 2P3F Health Literacy Program comprising Policy, Platform, Food, Fit, and Fulfilled on health literacy, overweight management behaviours, and body mass index (BMI) among late adolescents in Thailand. Methods: A quasi-experimental, two-group pre-test-post-test design was conducted among 76 late adolescents (aged 18-21 years) with overweight to class I obesity (BMI ≥ 23-29.9). Participants were assigned to either the experimental group (n = 38), which received a 12-week intervention, or the comparison group (n = 38), which received no intervention. Data was collected using validated questionnaires and BMI measurements. Paired and independent t-tests were used for data analysis. Results: After the intervention, the experimental group showed significantly higher scores in health literacy (Mean = 100.05, Mean diff = 27.12, 95% CI: 20.80 to 33.44), overweight management behaviour (Mean = 61.60, Mean diff = 20.00, 95% CI: 17.23 to 22.77), and a significantly lower BMI (Mean = 23.81 kg/m², mean diff = -2.69, 95% CI: -3.53 to -1.85) compared to the comparison group (P < 0.001 for all). Improvements were noted across all subdomains: access, understanding, appraisal, and application of health information. Conclusion: The 2P3F Health Literacy Program effectively improves health literacy and promotes healthier behaviours, reducing BMI among late adolescents. Nurses are vital in delivering digital health interventions and supporting adolescent health promotion through literacy-based strategies.